Efektivitas Penerimaan Negara dengan Penerapan Modul Penerimaan Negara Generasi Kedua Wilayah Kerja - Andy Priyambodo (Jurnal Ilmiah Ilmu Administrasi Publik, 2017)
State revenue is the most important part of the State Budget to finance various sectors of state expenditure. In support of this country's acceptance in apply MPN-G2 to facilitate the public in paying taxes. The result found that effectiveness of state revenue by applying of MPN-G2 system is quite effective in the case of quantity in the form of increasing percentage of amount of realization and transaction of state revenue. While the quality of state revenues after the MPN-G2 less effective because of input transparency of state revenue transactions is still too large so that the validity of the transaction is in doubt. For the duration of the state revenue with billing shows effective results because it is faster in the state revenue deposit, but the delegation of state revenue is less effective because it is still like the old system all transactions collected first with the time period determined after it was transferred to the state treasury. This study also produces factors that affect the effectiveness of state revenue with MPN-G2 such as communication, resources, and clarity of technology and procedures.